Ethnomatematics Exploration on Gondang Batak Musical Instruments Assisted by Geogebra - Frida Marta Argareta Simorangkir (UMSU, 2023)
This study aims to explore the mathematical concepts that exist in the Gondang Batak musical instrument with the help of Geogebra so that it can be implemented in learning. This study uses exploratory qualitative research related to the Gondang Batak musical instrument. The results of this study indicate that there is a flat shape concept and a spatial concept in the Gondang Batak musical instrument. This can also be demonstrated by using Geogebra so that students better understand the mathematical concepts of the Gondang Batak musical instrument. It can be concluded that the Gondang Batak musical instrument can be used as a medium for learning mathematics at the elementary and middle school levels. In addition, students can also learn Batak culture, especially related to the Gondang Batak musical instrument.